Middle management communication in the midst of a crisis - Mbolekwano, Veliswa A (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
Crisis communication by organisational top leadership to external stakeholders has been explored in literature, while internal crisis communication dynamics by middle managers with their employees within the organisation has been under studied. This paper pursues an understanding of crisis communication dynamics between middle management and their subordinates by investigating how the Middle Managers/Team Leaders of Makana Brick Manufacturing Firm (MBMF) communicated with their employees in the midst of the Eskom load shedding crisis in 2014. The investigation is not limited only to how they handled or made sense of the crisis, but also examines the effect and efficiency of their daily communication on both employees (subordinates) and operations in pursuing this end. As a foundation and background, the study broadly explores the literature on Crisis Leadership, Crisis and Crisis Communication, which are critical topics to understanding the communication role of the middle managers who were the primary subject of this research. The research was conducted through semi-structured, face-to-face interviews. Nine Team Leaders were interviewed. The data collected was transcribed verbatim and analysed through open coding. In the literature of crisis management, the concept of crisis communication has been extensively examined as a function of crisis management, primarily with regards to the crisis communication strategy, encompassing the actual verbal and nonverbal responses an organisation uses to address a crisis. The findings are generally congruent with the crisis communication literature, and reinforce the importance of efficient internal communication in building a culture of transparency between management and employees, as espoused in the literature reviewed, which in addition presents an invaluable opportunity for employees across all levels to engage in and be informed of the organisation's priorities and therefore has the potential to dictate the success or failure of any major change or crisis situation. As such, it can be argued that there is a need for the same analytical rigour that is given to external crisis communication to be given to financial or operational measures (Barrett, 2002). For both external and internal stakeholders, human compassion, concern and empathy; faith in legitimate and appropriate actions taken by the chosen organisation spokesperson; and honesty, candidness and openness in communication (Seeger 2006, p. 242) are universal. The quality and the quantity of communication, essentially, affect the level of trust and involvement of employees (Thomas, Zolin & Hartman, 2009), which is particularly relevant in times of crisis (Mazzei & Ravazzani, 2015 p. 322). Trust must be developed with staff through clear, honest communication and transparent actions. These encompass being fair, open in communication and intentions, showing consistency, fulfilling promises and being honest about what middle managers can and cannot communicate to their employees (Farrel & Schlesinger, 2013, p. 125). In this study, face to face communication proved to be the most preferred communication channel because of its rewarding advantages such as direct feedback, two-way communication, relationship building and project collaboration.
Keywords: Uncatalogued